A Language of Children with Disabilities in Digital Pattern Design - Dede Ananta K Perangin-angin; Martien Roos Nagara (Mudra Jurnal Seni Budaya, 2024)
Visual Language of Children with Special Needs in Digital Motif Design. This article aims to understand the designs made by children with special needs in the form of digital motifs done on adobe photoshop softweat. Data collection is done through direct observation, literature study and practice. This problem is analyzed using qualitative methods with a design thinking approach whichincludes empathize which is the initial stage carried out personally to children with special needs to get the right action, define the selection of tools or software that can help realize visual works in the form of digital design, ideate the stage of producing ideas in theform of moodboards which are set as a reference for realizing digital motif designs, prototype the initial design of digital motifs that stilllook static and can be used as the main sample of the creative process so that it can measure the suitability of the designed designconcept, and test is the final stage of testing carried out as a process of understanding from children with special needs using Adobe Photoshop softwear so as to produce digital motifs that look dynamic and in accordance with the designed concept. The result of this research is the visualization of digital motifs that have character and characteristics through hand strokes and sense or art owned bychildren with special needs and add to the diversity of design work, especially in the field of fashion in making digital motifs as an effort to raise the value of art and creativity created by children with special needs.